Promoter cloning and activities analysis of JmLFY, a key gene for flowering in Juglans mandshurica - Zhang, Lijie; Fu, Jingqi; Dong, Tianyi; Zhang, Mengmeng; Wu, Jingwen; Liu, Chunping (Frontiers in Plant Science, 2023)
Juglans mandshurica (Manchurian walnut) is a precious timber and woody grain and oil species in Northeast China. The heterodichogamous characteristics phenomenon resulted in the non-synchronous flowering and development of male and female flowers, which limited the mating and the yield and quality of fruits. LFY is a core gene in the flowering regulatory networks, which has been cloned in J. mandshurica and the function have also been verified preliminarily. Promoters determined the expression level of genes and occupy an important role in the regulation of gene transcription. In order to elucidate the molecular regulatory mechanism of JmLFY gene in the development process of J. mandshurica flowers, JmLFY promoter sequence (pLFY1) were cloned and conducted bioinformatics analysis. Transgenic tobacco plants with pLFY1 were obtained by Agrobacterium infection using pCAMBIA1301 expression vector, and the GUS gene driven by JmLFY promoter were detected to express in leaf, stem, flower and root of the tobacco plant, which indicated that the obtained JmLFY promoter had driving activity. The promoter sequence contains core cis-acting elements essential for eukaryotic promoters, hormone responsive elements, defense and stress responsive elements and flowering-related elements etc.. In order to identify the core regulatory regions of the JmLFY gene promoter and verify its activity and function, several promoter fragments with different length of 5’-deletion (pLFY1-pLFY6) were cloned and transformed transiently in to tobacco plants. GUS histochemical staining and enzyme activity detection showed that promoter fragments with different lengths had promoter activity, and could respond to the induction of long photoperiod, low temperature, SA, IAA, GA3 and MeJA. The core regulatory region of JmLFY gene promoter in J. mandshurica was between - 657bp and - 1904bp. Point-to-point validation of yeast single-hybrid confirmed the interaction between JmSOC1 and the JmLFY gene promoter, which indicated that JmLFY gene is the down stream target of JmSOC1. These results reveal relevant factors affecting JmLFY gene expression, and clarify the molecular mechanism of JmLFY gene regulation in the flower developmental partially, which will provide a theoretical basis for regulating the flowering time by regulating JmLFY gene expression in J. mandshurica.